Legal Analysis of Incest Marriage in the Suku Anak Dalam (SAD) Community in Rupit District, South Sumatra, Indonesia - Kusmawaningsih, Susi; Mauliyanti, Anita; Kloos, David; Azhari, Ari; Purnama Ratu, Liliany (Jurnal Mahkamah : Kajian Ilmu Hukum dan Hukum Islam, 2023)
This article examines incestuous marriage in the Suku Anak Dalam/SAD community from a legal perspective. Juridically, incestuous marriage is prohibited because it negatively affects the risk of children who can experience birth defects and a high risk of death due to lack of genetic variation and a weak immune system. Incest marriages in the SAD community are organised in a hereditary manner that has become a culture. The focus of the study of this article is to find out the reasons why the SAD community conducts incest marriages and how the law views the risks of incest marriages on the children born, especially in the SAD community. The type of research method is qualitative research with a phenomenological approach. This research was conducted in Sungai Jernih Village, Rupit Sub-district, North Musi Rawas Regency, data collection techniques through observation, interviews and documentation, data analysis techniques using an inductive framework with legal theories. The research findings show that one of the factors of incestuous marriage in the SAD community is the strong SAD customs. The Village Government in Sungai Jernih Village, Rupit Sub-district, North Musi Rawas Regency has tried to reach out to the interests of the chief or head of the community group to prevent inbreeding, but this has not been successful because the chief is very concerned with his community and the SAD community strictly adheres to customs. Incestuous marriage, which is still practised in the SAD community, aims to obtain offspring between their tribes and the culture of their ancestors is not lost, this is to continue the offspring so that the existence of SAD is maintained, even though incestuous marriage has a negative impact.